Effectiveness of smartphone and virtual reality based exergaming on mobility of stroke patients: A systematic review - Triensya, Rafiana; Kariasa, I Made; Arista, Liya; Waluyo, Agung (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Stroke is a leading cause of long-term disability and death worldwide. Recent advances in rehabilitation technology have introduced exergaming, a form of interactive physical therapy using digital games, as a promising intervention to enhance motor recovery. Purpose: To evaluate the effectiveness of smartphone and virtual reality based exergaming on mobility of stroke patients. Method: Systematic review research and article search were conducted through ScienceDirect, ProQuest, EBSCOhost (Medline), SAGE Journals, and PubMed databases. The review and synthesis process used the PRISMA diagram guide. Results: Based on the review of 7 literatures obtained, it shows that the majority reported significant improvements in patient mobility after exergaming interventions, especially those using smartphone applications and virtual reality (VR) platforms. Conclusion: Smartphone-based exergaming and virtual reality (VR) are effective and attractive therapeutic approaches to improve mobility in stroke rehabilitation. Keywords: Exergaming; Mobility; Smartphone; Stroke Patients; Virtual Reality. Pendahuluan: Stroke adalah penyebab utama kecacatan dan kematian jangka panjang di seluruh dunia. Kemajuan terbaru dalam teknologi rehabilitasi telah memperkenalkan exergaming bentuk terapi fisik interaktif menggunakan permainan digital sebagai intervensi yang menjanjikan untuk meningkatkan pemulihan motorik. Tujuan: Untuk mengevaluasi efektivitas latihan berbasis telepon pintar dan realitas virtual terhadap mobilitas pasien stroke. Metode: Penelitian systematic review dan pencarian artikel dilakukan melalui database ScienceDirect, ProQuest, EBSCOhost (Medline), SAGE Journals, dan PubMed. Proses review dan sintesis menggunakan panduan diagram PRISMA. Hasil: Berdasarkan review dari 7 literatur yang didapatkan, menunjukkan bahwa mayoritas melaporkan peningkatan yang signifikan dalam mobilitas pasien setelah intervensi exergaming, terutama yang menggunakan aplikasi ponsel pintar dan platform realitas virtual. Simpulan: Exergaming berbasis smartphone dan virtual reality (VR) merupakan pendekatan terapi yang efektif dan menarik untuk meningkatkan mobilitas dalam rehabilitasi stroke. Kata Kunci: Exergaming; Mobility; Smartphone; Stroke Patients; Virtual Reality.